128k views
2 votes
Explain who to write a quadratic equation that has -6 as its only root

User Blag
by
6.6k points

1 Answer

3 votes
If you have the equation
x2 + 2x - 3 = 0
You can factor the quadratic to get
(x - 1)(x + 3) = 0
and hence the roots
x = 1 and x = -3

Conversely, if you have the roots x = 1 and x = -3 you can recover the quadratic equation by forming (x - 1)(x + 3) = 0.

(x - 5 - 3i)(x - 5 + 3i) = 0
which simplifies to
x2 - 10x + 34 = 0

hope this helped :)
alisa202
User Shawkath Srijon
by
6.3k points